Changes in the Reproductive Traits of Low-chill Peach Tree in Response to Reproductive Shoot Pruning after Harvesting - Weber, M. (2013)
ABSTRACT: At the central-east area of the Santa Fe province (Argentina), early maturing peach varieties characterised by a long remaining growing season after harvest are used. The aim of this works was to study the effects of fruit-bearing shoots renovation, performed just after harvest, on different vegetative and reproductive parameters of peach tree, in comparison with the traditional winter pruning. After harvest, a group of plants remained unpruned as control trees (T0), whereas another group was pruned (T1). Pruning consisted of heading back or thinning out the recently harvested bearing shoots. Green pruning significantly increased the relative radiation measured in the canopy for more than 80 days after pruning, modifying the architecture of the aerial part of the tree. The relative proportion of the different bearing shoots was not affected by pruning treatment but green pruning increased the proportion of mixed shoots that arose from the main tree scaffold (+15%) and those that were inserted in the intermediate strata of plant height. Trees pruned after harvest were able to compensate the leaf area removed by the emission of new branches (+108%) in the remained shoots, but were unable to compensate TCA annual evolution (-37.4%) and plant size (?7 to -26%). Green pruning extended the vegetative growth period during autumn, delaying leaf senescence (+10 days) and dormancy induction. Tree yield and fruit size were not affected by pruning treatments.